Entrepreneurship - Hirsch, Robert D; Peters, Michael P; Shepherd, Dean A (Boston : McGraw-Hill, 2005)
Photocopy
Includes index
Keywords: New business enterprises; Entrepreneurship; Business planning; Success in business